2019
DOI: 10.1155/2019/8151087
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Novel Energy‐Dissipating Prefabricated Beam‐Column Joints

Abstract: A new dapped-end beam to column connection is designed in this paper. Its assembly connection zone changes from inside the joint to midspan of the beam. The proposed connection can not only provide good structural integrity but also ensure that the plastic hinge moves away from the column edge. The rotational capacity of the plastic hinge determines the internal force redistribution of the joint and the energy dissipation capacity. The high-strength bolts and steel plates are used to realize connection, furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 31 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…e structural prototype in this study is a fabricated RCS composite frame structure (five-storey, 3 × 4-bay), which is designed in accordance with the requirements of Chinese building codes [23][24][25][26][27]. Live and dead load values on floors and roof are 2.0 and 2.0 KN/ m 2 , respectively.…”
Section: Experimental Perspectivementioning
confidence: 99%
“…e structural prototype in this study is a fabricated RCS composite frame structure (five-storey, 3 × 4-bay), which is designed in accordance with the requirements of Chinese building codes [23][24][25][26][27]. Live and dead load values on floors and roof are 2.0 and 2.0 KN/ m 2 , respectively.…”
Section: Experimental Perspectivementioning
confidence: 99%
“…Therefore, the hard roof has always been a problem for safe and efficient mining in coal mines. To solve the hard roof problem in coal mines, many scholars have conducted in‐depth research and proposed various hard roof control technologies, such as ground fracturing, hydraulic fracturing, concentrated blasting, water injection softening, and so forth 2–4 . These technologies have achieved very good control results for hard roofing.…”
Section: Introductionmentioning
confidence: 99%
“…proposed various hard roof control technologies, such as ground fracturing, hydraulic fracturing, concentrated blasting, water injection softening, and so forth. [2][3][4] These technologies have achieved very good control results for hard roofing.…”
mentioning
confidence: 99%
“…[29][30][31][32]. Presently, investigations on the behaviors of prefabricated structures under the shear load, flexural load, and cyclic load have been conducted [33][34][35][36]. Ding et al [37] study the seismic performance of a semi-rigid connector between autoclaved lightweight concrete (ALC) panel and steel frame, which showed that the use of the semi-rigid connector can effectively reduce the damage of ALC panel.…”
Section: Introductionmentioning
confidence: 99%